Low Risk for Switch to Mania during Treatment with Sleep Promoting Antidepressants - Wichniak, A.; Jarkiewicz, M.; Okruszek, Ł.; Wierzbicka, A.; Holka-Pokorska, J.; Rybakowski, J. K. (Pharmacopsychiatry, 2015)
Introduction: Sleep-promoting antidepressants are of interest because they are used not only as antidepressants, but also to promote sleep.Methods: We reviewed case reports describing the switch to mania during treatment with trazodone, mirtazapine, or agomelatine.Results: Trazodone, mirtazapine, and agomelatine may induce manic symptoms. However, the risk of switching is related, first of all, to doses recommended for antidepressant treatment, administered without mood-stabilizer co-therapy. Low doses of these antidepressants, used for their hypnotic or sedative effects, were observed to cause mania only in patients with other risk factors for switching. There is no evidence for trazodone or mirtazapine and only sparse evidence for agomelatine, claiming that treatment with these antidepressants is related to an increased risk of switching to mania when administered in combination with a mood stabilizer.Discussion: These findings suggest that low doses of trazodone and mirtazapine are safe in bipolar disorder, and should still be considered important alternatives to hypnotics when long-term pharmacological treatment of insomnia is necessary. It seems that these antidepressants and agomelatine can also be used safely in antidepressant doses when combined with a mood stabilizer.
Keywords: bipolar disorder; switch to mania; antidepressants; trazodone; mirtazapine; agomelatine